Geomagnetically Induced Current Analysis in Malaysian Power Transmission System - Khurshid Z.M.; Ab Aziz N.F.; Rhazali Z.A.; Ab Kadir M.Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric fields; Electric grounding; Electric network analysis; Electric power transmission networks; Electric substations; Intercalation; Power transformers; Reactive power; Risk assessment; Solar energy; Timing circuits; Circuit faults; Conductivity; Geomagnetic disturbance; Geomagnetically induced currents; High voltage techniques; High-voltage transformers; Malaysian power network; Malaysians; Power; Power grids; Power networks; Power system; PSCAD/EMTDC; Space weather; Substation; Geomagnetism